Urban agriculture as a climate change and disaster risk reduction strategy - Veenhuizen, D.M.R. van; Halliday, J.C.T. (RUAF Foundation, 2019)
Urban and peri-urban agriculture is considered as a strategy that can bring multiple benefits and help to build resilient urban food systems at the city region level. Cities have an important role to play in climate change mitigation and adaptation, disaster risk management and in enhancing the climate resilience of their vulnerable residents. Major emitters of greenhouse gas (GHG), cities are not only contributing to climate change, but are also directly and indirectly impacted by it. Acute or chronic climate change is threatening access to basic urban services such as water, energy and food for growing populations. Key issues include rising temperatures, increasing rainfall, flooding and urban food insecurity. Rapid urban growth will only increase the number of highly vulnerable urban communities, with the urban poor being most at risk. Only with a coordinated approach and action at the global, regional, national and local levels can the climate change emergency be curbed, and its eff ects mitigated.